Creation of new cities in Peru 1960 - 2017: the planning failed and the informal endure? - Castillo García, Rodolfo Francisco (2022)
The objective of this article is to make some reflections about the paradox that efforts of planned growth of cities in Peru usually fail or disappear, while the mess and the informality endure. To do this, we make a brief summary of some experiences of creating new cities in the country and how they finished, also about how it was considered or should be considered this issue from urban public policies, with some final recommendations.